Pengaruh Strategi Bisnis dan Ketidakpastian Lingkungan terhadap Hubungan antara Informasi Broad Scope Sistem Akuntansi Manajemen dan Kinerja Manajerial - Ernawati, Ernawati (Journal of Accounting and Investment, 2016)
This study intends to give the empirical evidence on interaction effect of information of broad scope management accounting system with business strategy and eviromental uncertainty on managerial performance. Business strategy and enviromantal uncertainty were used in this study as moderating variable. First hypothesis used business strategy, meanwhile second hypothesis used enviromental uncertainty. Questionnaires were distributed to fifteen manufacturing companies in Surakarta with convinience sampling method. The responses from 44 production manager, distribution manager and general manager, were analysed using the hierarchical regression (moderated multiple regression). The result support the hypothesis that the interaction effect of broad scope management accounting system information with business strategy and enviromental uncertainty on managerial performance are positive and significant. For the company employing a business strategy of prospector will be more positive than the company employing business strategy of defender. Then, the effect of broad scope management accounting system information will be more positive under high level of enviromental uncertainty than lower level enviromental uncertainty.